Social Feedback During Sensorimotor Synchronization Changes Salivary Oxytocin and Behavioral States - Papasteri, Claudiu C.; Sofonea, Alexandra; Boldasu, Romina; Poalelungi, Cǎtǎlina; Tomescu, Miralena I.; Pistol, Constantin A. D.; Vasilescu, Rǎzvan I.; Nedelcea, Cǎtǎlin; Podina, Ioana R.; Berceanu, Alexandru I.; Froemke, Robert C.; Carcea, Ioana (Frontiers in Psychology, 2020)
In humans and animal models, oxytocin increases social closeness, attachment and prosocial behaviors, while decreasing anxiety and stress levels. Efficiently triggering the release of endogenous oxytocin could serve as a powerful therapeutic intervention for disorders of social behavior and for anxiety. We designed a new version of a social sensorimotor synchronization task to investigate the role of social approval in inducing biochemical and psychological changes following behavioral synchrony in a sample of 80 college students. Social approval in the form of real time positive feedback increased well-being only in women, while increasing social closeness in both genders. Social disapproval in the form of real time negative feedback prevented a decrease in stress levels that otherwise women reported following engagement in either social or non-social synchronization. Surprisingly, for certain personality traits, negative social feedback during sensorimotor synchronization was psychologically beneficial irrespective of gender. Salivary oxytocin levels increased only in women after the social but not the non-social synchronization tasks. Oxytocin dynamics were independent of the type of real time feedback that subjects received, indicating the existence of distinct mechanisms for hormonal versus behavioral changes following synchronization. Nevertheless, changes in salivary oxytocin after positive social feedback correlated with changes in well-being and predicted changes in prosocial attitudes. Our findings show evidence of distinct mechanisms for behavioral versus hormonal changes following social sensorimotor synchronization, and indicate that gender and personality traits should be carefully considered when designing behavioral therapies for improving social attitudes and for stress management.